From Seaweed to Chemicals: A Guide to Organic Compounds for Vocational High School Students - Sari, Nur Indah; Musthapa, Iqbal; Eko, Ratnaningsih; Ahmad, Fandi (Journal of Vocational Education Studies, 2025)
This study aims to produce an organic compound textbook for the Seaweed Agribusiness Expertise Program at vocational high schools. The research method used is a mixed method with an educational reconstruction model that focuses on content structure analysis. Content structure analysis is carried out through literature studies, subject matter clarification, and concept modification and refinement. Validation by experts was carried out to see the suitability of the indicators and learning objectives, as well as the suitability of the textbook with the BSNP criteria. The characteristics of the resulting textbook use problem-based learning syntax. The textbook consists of four chapters and several sections related to the expertise program, in the form of knowledge, information, and applications about seaweed. The assessment of the textbook includes the suitability of the learning objectives with the text in the textbook. The results of the expert assessment of the textbook show the suitability of the indicators with the learning objectives and the suitability of the learning objectives with the textbook text. All indicators and learning objectives obtained a CVR value calculated above the critical CVR value of 0.622 for seven validators, namely CVR = 1.00, so that it can be accepted or declared valid. The suitability of the textbook with quality criteria based on BNSP includes the aspects of content feasibility, presentation feasibility, language and graphics with percentages of 86.68%, 94%, 100%, and 100%, respectively. The results of this study indicate that the developed organic compound textbook has met the validity criteria and is feasible for use in learning in vocational high schools with the Seaweed Agribusiness Expertise Program. This textbook is expected to be a reference for vocational high school students to improve their understanding of the organic compounds found in seaweed so that they can be utilized in seaweed cultivation and processing practices.